2021
DOI: 10.21037/tau-20-1067
|View full text |Cite
|
Sign up to set email alerts
|

Peyronie’s disease may negatively impact the sexual experience of a couple and female sexual function: a single center study

Abstract: Background: Peyonie's disease (PD) mostly affects males in the fifth decade of life, with a prevalence in the general population ranging between 0.5% and 20.3%. The pathology of PD is characterized by fibrosis of the tunic albuginea of the cavernous bodies of the penis, with the presence of pain in the erection and penile deformity. This is associated with decreased sexual function for both participants. The objective of the study was to investigate the influence of PD pathology on both male patients' and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…PD presents with concomitant erectile dysfunction (ED) in 40-50% of men. The physical manifestations of PD contribute to the development of emotional distress and relationship problems (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…PD presents with concomitant erectile dysfunction (ED) in 40-50% of men. The physical manifestations of PD contribute to the development of emotional distress and relationship problems (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Our study had shown that the sexual function of female partners was significantly improved compared to baseline especially desire, arousal, orgasm, and overall satisfaction except some of their sexual functions including frequency of satisfaction with arousal, frequency of lubrication, difficulty of becoming lubricated, and finally maintenance of lubrication that were not positively impacted which implies treating their male partners. Similarly, Illiano et al 22 had demonstrated that a viable approach to treatment of Peyronie's disease patients that included their partners could lead to better functional and psychological results in both of them. Remarkably, the low scores of the female partners in our study can be a subjective experience of sexual well-being rather than distress as they were healthy.…”
Section: Discussionmentioning
confidence: 99%
“…PD occurs in 3.2% to 8.9% of the male population, and it typically presents at 55 to 60 years of age; however, it can occur at any age [ 6 , 7 ]. Traditionally, men with PD experience pain during sexual intercourse, erectile dysfunction, and emotional and physical distress [ 8 ]. Furthermore, erectile dysfunction caused by pathological disease progression greatly affects the sexual activity of men and their partner [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, men with PD experience pain during sexual intercourse, erectile dysfunction, and emotional and physical distress [ 8 ]. Furthermore, erectile dysfunction caused by pathological disease progression greatly affects the sexual activity of men and their partner [ 8 ].…”
Section: Introductionmentioning
confidence: 99%